2017
DOI: 10.1186/s12878-017-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaemia and Associated Risk Factors among Children in North-western Uganda: A Cross Sectional Study

Abstract: BackgroundDespite the public health significance of anaemia in African children, its broader and often preventable risk factors remain largely under described. This study investigated, for the first time, the prevalence of childhood anaemia and its risk factors in an urban setting in Uganda.MethodsA total of 342 children were enrolled. Venous blood samples were collected in EDTA tubes and analyzed using Symex 500i (Symex Corp. Japan). Stool and urine samples were analyzed according to established standard meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 37 publications
10
31
3
1
Order By: Relevance
“…Consequently, larger families could have a higher socio‐economic status and more resources for children, as well as a stronger social support network, important for the care of infants and toddlers at home. This finding is aligned with a recent cross‐sectional analysis in Uganda that found that larger households had higher incomes, and children living in these households had a lower probability of anaemia (Legason, Atiku, Ssenyonga, Olupot‐Olupot, & Barugahare, ).…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, larger families could have a higher socio‐economic status and more resources for children, as well as a stronger social support network, important for the care of infants and toddlers at home. This finding is aligned with a recent cross‐sectional analysis in Uganda that found that larger households had higher incomes, and children living in these households had a lower probability of anaemia (Legason, Atiku, Ssenyonga, Olupot‐Olupot, & Barugahare, ).…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of anaemia was 15.4% in this study, which does not markedly differ from other studies carried out in northern Ethiopia (11%) [ 31 ], north-western Uganda 11.8% [ 32 ] and northwestern Morocco (16.2%) [ 33 ]. But it was lower than the reports from Shimbit, Ethiopia (25.8%) [ 6 ]; Jimma, Ethiopia (37.6%) [ 4 ]; Kenya (28.8%) [ 34 ]; Rwanda (30.9%) [ 35 ] and Upper Egypt (59.3%) [ 36 ].…”
Section: Main Textcontrasting
confidence: 73%
“…Low serum retinol status is an indicator of vitamin A deficiency; participants with low serum retinol concentration were 1.7 times more likely to be anaemic compared to those with normal serum retinol. e findings give support to existing knowledge that the causes of anaemia are multifactorial [36][37][38][39].…”
Section: Journal Of Nutrition and Metabolismsupporting
confidence: 86%